Multi-Omics Sequencing Provides Insights Into Age-Dependent Susceptibility of Grass Carp (Ctenopharyngodon idellus) to Reovirus - He, Libo; Zhu, Denghui; Liang, Xinyu; Li, Yongming; Liao, Lanjie; Yang, Cheng; Huang, Rong; Zhu, Zuoyan; Wang, Yaping (Frontiers in Immunology, 2021)
Grass carp (Ctenopharyngodon idellus) is an important aquaculture species in China that is affected by serious diseases, especially hemorrhagic disease caused by grass carp reovirus (GCRV). Grass carp have previously shown age-dependent susceptibility to GCRV, however, the mechanism by which this occurs remains poorly understood. Therefore, we performed transcriptome and metabolome sequencing on five-month-old (FMO) and three-year-old (TYO) grass carp to identify the potential mechanism. Viral challenge experiments showed that FMO fish were susceptible, whereas TYO fish were resistant to GCRV. RNA-seq showed that the genes involved in immune response, antigen presentation, and phagocytosis were significantly upregulated in TYO fish before the GCRV infection and at the early stage of infection. Metabolome sequencing showed that most metabolites were upregulated in TYO fish and downregulated in FMO fish after virus infection. Intragroup analysis showed that arachidonic acid metabolism was the most significantly upregulated pathway in TYO fish, whereas choline metabolism in cancer and glycerophospholipid metabolism were significantly downregulated in FMO fish after virus infection. Intergroup comparison revealed that metabolites from carbohydrate, amino acid, glycerophospholipid, and nucleotide metabolism were upregulated in TYO fish when compared with FMO fish. Moreover, the significantly differentially expressed metabolites showed antiviral effects both in vivo and in vitro. Based on these results, we concluded that the immune system and host biosynthesis and metabolism, can explain the age-dependent viral susceptibility in grass carp.